Answer:
The arithmetic combinations of given functions are (f + g)(x) = 2x, (f - g)(x) = 4, (f
g)(x) =
,
![\left((f)/(g)\right)(\mathrm{x})=(x+2)/(x-2)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/ulnmagakers1kcf16h7yznh1kjn4q3n8du.png)
Solution:
Given, two functions are f(x) = x + 2 and g(x) = x – 2
We need to find the arithmetic combinations of given two functions .
Arithmetic functions of f(x) and g(x) are (f + g)(x), (f – g)(x), (f
g)(x),
![\left((f)/(g)\right)(\mathrm{x})](https://img.qammunity.org/2020/formulas/mathematics/middle-school/tsk8shmyssczo55oghyzwjk9e6x4elpo91.png)
Now, (f + g)(x) = f(x) + g(x)
= x + 2 +x – 2
= 2x
Therefore (f + g)(x) = 2x
similarly,
(f - g)(x) = f(x) - g(x)
= x + 2 –(x – 2)
= x + 2 –x + 2
= 4
Therefore (f - g)(x) = 4
similarly,
(f
g)(x) = f(x)
g(x)
= (x + 2)
(x – 2)
= x
(x – 2) + 2
(x -2)
![=x^(2)-2 x+2 x-4](https://img.qammunity.org/2020/formulas/mathematics/middle-school/iuv6uyv2gcg6r0o79e2cy7mvur0fc4w1yy.png)
![=x^(2)-4](https://img.qammunity.org/2020/formulas/mathematics/middle-school/kk0koyb1waipcx7864myhfkexvw07b3d39.png)
Therefore (f
g)(x) =
![x^(2)-4](https://img.qammunity.org/2020/formulas/mathematics/middle-school/5221sjlesq3w3xori69hxr5wgqkhop07cn.png)
now,
![\left((f)/(g)\right)(\mathrm{x})=(f(x))/(g(x))](https://img.qammunity.org/2020/formulas/mathematics/middle-school/o8bxvbm35zfi8448051nr6x5t7goi1ih2i.png)
![=(x+2)/(x-2)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/itvpsy37iuugzifz9nbs4ig6f9bvxnxxu3.png)
=
![(x+2)/(x-2)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/zysww1tnt9q13kr5dqcjcsxed3b82rdbbx.png)
Hence arithmetic combinations of given functions are (f + g)(x) = 2x, (f - g)(x) = 4, (f
g)(x) =
,
![\left((f)/(g)\right)(\mathrm{x})=(x+2)/(x-2)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/ulnmagakers1kcf16h7yznh1kjn4q3n8du.png)